PENINGKATAN KUALITAS PELAYANAN DALAM MENANGANI PENGIRIMAN PAKET KONSUMEN DI JNT CARGO PONOROGO - Rahmad Hidayat; Naning Kristiyana (Universitas Muhammadiyah Ponorogo, 2026)
This community service activity aims to implement programs and improve service quality at JNT Cargo Ponorogo with a focus on responsiveness. The improvement program focused on service speed, package data collection accuracy, and improved communication between employees and customers. The implementation results showed increased service process efficiency, a decrease in data collection errors, and improved quality of interactions with customers. Service improvements also resulted in an increase in the number of customers, package tonnage, and the achievement of operational targets compared to the previous month. Overall, the service quality improvement program proved effective in improving operational performance and customer satisfaction at JNT Cargo Ponorogo. Keywords : service quality, responsiveness, customer satisfaction, JNT Cargo Ponorogo